1998
DOI: 10.2190/ga2m-fla2-17fb-v5pe
|View full text |Cite
|
Sign up to set email alerts
|

A History of Medical Scientists on High Heels

Abstract: For 250 years medical scientists have propagandized about the health hazards of high-heeled shoes, which originated four centuries ago. Physicians, however, largely unaware of their own profession's tradition, keep reinventing the diagnostic wheel. This professional amnesia has held back the momentum of the process of educating the public. Consequently, despite these warnings, millions of women continue to wear high-heeled shoes. This article describes the history of the medical profession's recognition of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 25 publications
(22 reference statements)
0
25
0
4
Order By: Relevance
“…Raised heels tend to force the toes into the end of the shoe and so, when coupled with a pointed-toe design, are particularly deleterious to podiatric health. These did not appear until the 17th century (Linder and Saltzman, 1998).…”
Section: Patterning In the Frequency Of Hallux Valgus In The Study Mamentioning
confidence: 99%
“…Raised heels tend to force the toes into the end of the shoe and so, when coupled with a pointed-toe design, are particularly deleterious to podiatric health. These did not appear until the 17th century (Linder and Saltzman, 1998).…”
Section: Patterning In the Frequency Of Hallux Valgus In The Study Mamentioning
confidence: 99%
“…Tight and skinny wears can compress the nerves in body where nerves are superficial and having potential areas for compression [3]. High heel wearing is increasing in this era of fashion [4].…”
Section: Introductionmentioning
confidence: 99%
“…High-heeled shoe has been a popular footwear accessory for nearly 300 years and are used on a daily basis for 39% to 69% of female (Linder & Saltzman 1998). It has demonstrated that high-heeled shoes could cause potential dangers, such as abnormal plantar pressure distribution, leading to plantar forefoot pain, hallux valgus, and metatarsalgia (Dawson et al 2002;Cong et al 2011).…”
Section: Introductionmentioning
confidence: 99%